Characterization of the Flash-LED Lamp: EBNeuro Used to AcquiredVisual Evoked Potentials in Rats - Ortiz-Arzate, Z.; Camacho-López, M. A.; Ballesteros-Zebadua, P.; Franco-Pérez, J.; Treviño-Palacios, C.; Oros-Pantoja, R. (Revista Mexicana de Ingenieria Biomedica, 2018)
Signal amplitude for recordings of Visual Evoked Potentials (VEPs) is a variable dependent on the type and position of the electrodes, the source, the stimulus and consequently the luminous intensity; therefore, it is relevant to report it to assure experimental reproducibility. The objective of this work is to characterize a flash lamp with 96 LEDs in order to perform the acquisition of VEPs in rats. We measured the illuminance and mean light intensity on a space system XYZ of 8 cm3 corresponding to a stereotaxic frame for rodents. Displacements were performed every 2 cm in each plane. Because of the geometric distribution of the LEDs in the EBNeuro lamp the spatial distribution of illuminance does not follow the law of the inverse square, because the illuminance increases with the distance to the lamp. Finally a spatial coordinate was selected for the rat eye positioning were the mean luminous intensity was 1.043 cd and 128.77 luxes of illuminance at an eye-lamp distance of 9 cm. According to the obtained VEPs and spatial characterization this lamp can be used for the acquisition of recordings PEV in rats for further investigations.